Designing Contextual Mathematics Tasks to Enhance Numeracy Skills of Grade 5 Primary School Students at SD Negeri Mijen 2 - Aulia Zulfa (CV. Ulil Albab Corp, 2026)
This study aims to develop and evaluate contextual mathematics tasks to enhance the numeracy skills of Grade 5 primary school students at SD Negeri Mijen 2. The research employed a Research and Development (R&D) approach combined with a quasi-experimental one-group pretest–posttest design. The development process followed the ADDIE model (analysis, design, development, implementation, and evaluation). Participants consisted of 19 fifth-grade students from SD Negeri Mijen 2. Data were collected using a numeracy test instrument, classroom observation sheets, and student response questionnaires. Quantitative data were analyzed using descriptive statistics, percentage gain, normalized gain (N-gain), and a paired-sample t-test. The results indicate a statistically significant improvement in students’ numeracy skills, with the mean score increasing from 63.16 on the pretest to 82.11 on the posttest, representing an improvement of 18.95 points (30.00%). The N-gain score was 0.52 (moderate category), and the paired-sample t-test revealed a significant difference (t(18) = 9.87, p < 0.001). These findings suggest that contextual mathematics tasks are effective in improving numeracy skills among primary school students.